STUDI KORELASIONAL PENGETAHUAN KEARIFAN LOKAL, SIKAP TERHADAP LINGKUNGAN, DAN MOTIVASIONAL KONSERVASI DENGAN PARTISIPASI PEMUDA DALAM KONSERVASI PESISIR - Sihadi Darmo Wihardjo; Agus Sujarwanta (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2016)
The objective of this research to determine the relationship between indigenous knowledge, attitudes toward the environment, and conservation motivational with the participation of youth in resources conservation of coastal. The research was conducted at Cibalong Coastal Village, South Garut, 2015 with sum of samples 170 selected randomly. The research findings are as follow: (1) there is positive correlation between of indigenous knowledge with the participation of youth in resources conservation of coastal, (2) there is positive correlation between attitudes toward the environment with the participation of youth in resources conservation of coastal, (3) there is positive correlation between of conservation motivational with the participation of youth in resousrces conservation of coastal, and (4) there is positive correlation between of indigenous knowledge,  attitudes toward the environment, and conservation motivational  with the participation of youth in resources conservation of coastal.